Hermeneutic Cognition as Understanding: the Third Dimension of Reality - Paulikaitė, Milda (Problemos, 2003)
To scientific cognition of natural science Gadamer opposes hermeneutical understanding that differs from the former by its attitude to the world. Conception of cognition undergoes essential and radical change. It can be described in many aspects. In this paper I am concentrating my attention on the notion of reality. Gadamer considers human facticity and finitude as the main precondition and the only source of the hermeneutical understanding. In the experience of human facticity the reality unfolds itself. It is real in the most personal sense of one?s life. Life is not theoretical scheme that can be constructed freely by subject?s will. It is the meeting with the reality in the factical experience of existence.
Keywords: Gadamer; hermeneutics; fmitude of subject; reality